Post-monsoon waterlogging-associated upsurge of cholera cases in and around Kolkata metropolis, 2015. (2019) - Mukhopadhyay, Asish K.; Deb, Alok K.; Chowdhury, Goutam; Debnath, Falguni; Samanta, Prosenjit; Saha, Rudra Narayan; Manna, Byomkesh; Bhattacharya, Mihir K.; Datta, Dharitri; Okamoto, Keinosuke; Bhadra, Uchhal K.; Dutta, Shanta
Abstract: The Infectious Diseases and Beliaghata General Hospital, Kolkata, India witnessed a sudden increase in admissions of diarrhoea cases during the first 2 weeks of August 2015 following heavy rainfall. This prompted us to investigate the event. Cases were recruited through hospital-based surveillance along with the collection of socio-demographic characteristics and clinical profile using a structured questionnaire. Stool specimens were tested at bacteriological laboratory of the National Institute of Cholera and Enteric Diseases (NICED), Kolkata. Admission of 3003 diarrhoea cases, clearly indicated occurrence of outbreak in Kolkata municipal area as it was more than two standard deviation of the mean number (911;s.d. = 111) of diarrhoea admissions during the same period in previous 7 years. Out of 164 recruited cases, 25% were under-5 children. Organisms were isolated from 80 (49%) stool specimens. Vibrio cholerae O1 was isolated from 50 patients. Twenty-eight patients had this organism as the sole pathogen. Among 14 infants, five had cholera. All V. cholerae O1 isolates were resistant to nalidixic acid, followed by co-trimoxazole (96%), streptomycin (92%), but sensitive to fluroquinolones. We confirmed the occurrence of a cholera outbreak in Kolkata during August 2015 due to V. cholerae O1 infection, where infants were affected.